Overview of Risk Factors for Stroke in Stroke Patients in Work Area at Technical Implementation Unit of the Linggang Bigung Public Health Centre - Karlina, Nova; Tini, Tini; Purwanto, Edi (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Stroke is one of the main health problems, not only in Indonesia but in the world. Stroke occurs when the brain's blood vessels experience a blockage or rupture which results in part of the brain not getting the blood supply that carries the necessary oxygen so that cell/ tissue death occurs.  Objective: The purpose of this study was to determine the risk factors for Stroke in Stroke patients in the Linggang Bigung Health Center working area.  Methods: This study used a descriptive retrospective research design, with a sample size of 22 respondents. Results and Discussion: The results of the study obtained as many as 7 respondents (32%) each with the latest education not in school and elementary school. The majority of 14 respondents (65%) were >55 years old, with the majority of 13 respondents (59%) being male, 16 respondents (73%) had no family history of Stroke, in this study all respondents had hypertension, 13 respondents (59%) had DM, 18 respondents (82%) each smoked and consumed alcohol, while 21 respondents (95%) were not obese.  Conclusion: In this study most, respondents were aged >55 years, male gender, had smoking behavior and alcohol consumption and all respondents in this study had hypertension.